Game-based religious character building efforts for kindergarten teachers and students in Lorok Village, Ogan Ilir Regency - Ermanovida Ermanovida; Aulia Utami Putri; Yosi Arianti; Dwi Mirani; Norma Juainah (Community Empowerment, 2022)
The main objective of this community service is to teach religious character building to children in Lorok Village, Ogan Ilir Regency's Kindergarten/TPA. The method used, which included learning while playing with a song balloon game, ranking one, and a battle of wits, focused on civic education and the development of religious character. The results of this activity include an increase in students' religious character, as evidenced by the results of each teacher's assessment while accompanying the contestants, as well as a high level of enthusiasm among students for learning while playing, implying that this game method provides learning innovation for teachers.